1995
DOI: 10.1113/expphysiol.1995.sp003850
|View full text |Cite
|
Sign up to set email alerts
|

Opioid tolerance and dependence in the magnocellular oxytocin system: a physiological mechanism?

Abstract: At the neurosecretory terminals in the neural lobe, oxytocin secretion is restrained by co‐secreted endogenous opioids, which act via kappa‐receptors. The co‐secreted opioids include products of pro‐dynorphin (released by both vasopressin and oxytocin terminals) and proenkephalin (released by oxytocin terminals). In morphine‐tolerant rats this opioid mechanism is more effective, but in late pregnancy it is less effective. Opioids also act directly on oxytocin cell bodies, via separate mu‐ and kappa‐receptors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 119 publications
1
50
0
2
Order By: Relevance
“…Our finding in a few terminals that administration of -opioids attenuated depolarization-evoked C m responses despite little or no decrease in the associated Ca 2ϩ currents raises the additional possibility that opioids might regulate vesicle fusion and/or trafficking independently of Ca 2ϩ current modulation. In any event, the present results suggest a potential mechanism whereby endogenous release of prodynorphin-derived opioid peptides, known to be colocalized in AVP-and OT-containing terminals (Zhao et al, 1988b;Russell et al, 1995), can exert inhibitory modulation of neuropeptide release from the neurohypophysis.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Our finding in a few terminals that administration of -opioids attenuated depolarization-evoked C m responses despite little or no decrease in the associated Ca 2ϩ currents raises the additional possibility that opioids might regulate vesicle fusion and/or trafficking independently of Ca 2ϩ current modulation. In any event, the present results suggest a potential mechanism whereby endogenous release of prodynorphin-derived opioid peptides, known to be colocalized in AVP-and OT-containing terminals (Zhao et al, 1988b;Russell et al, 1995), can exert inhibitory modulation of neuropeptide release from the neurohypophysis.…”
Section: Discussionmentioning
confidence: 62%
“…Opioids also depress neuropeptide release from the posterior pituitary, acting directly on vasopressin-(AVP) and oxytocin (OT)-containing neurons in the hypothalamus (Wuarin and Dudek, 1990;Renaud et al, 1992;Russell et al, 1995) and through presynaptic receptors located on their neurosecretory endings in the neurohypophysis (Zhao et al, 1988b;Kato et al, 1992). Although it remains unclear how the presynaptic inhibitory effects of opioids are manifested, measurements from neuronal somata suggest that the depression of release may result from reductions in Ca 2ϩ influx through voltage-dependent Ca 2ϩ channels (North, 1993).…”
Section: Abstract: -Opioid Receptor; Ca 2ϩ Currents; Membrane Capacimentioning
confidence: 99%
“…Following an osmotic challenge, dynorphin mRNA levels increase in the SON and the PVN (31-33), but dynorphin-like immunoreactivity in the posterior pituitary is reduced following prolonged salt-loading, suggesting peptide release (34). Dynorphin, co-released with VP, is probably a local modulator of neurosecretion in the neural lobe (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…The PVN and SON project to the posterior pituitary, where OT and AVP are secreted directly into the systemic circulation (Hatton, 1990). In vivo studies demonstrated that the opioid systems participate in regulation of the electrical activity of the OT and AVP neurons and the release of both hormones (Russell et al, 1995;Brown and Leng, 2000). The -opioid receptor agonists decreased the basal levels of both OT (Clarke et al, 1979;Frederickson et al, 1981;Clarke and Patrick, 1983;Hartman et al, 1987) and AVP (Van Wimersma Greidanus et al, 1979;Aziz et al, 1981).…”
Section: Modulation Of Serotonin Transmissionmentioning
confidence: 99%